Uhl's anomaly: perspective of fetal echocardiography and histopathological correlation. (30th August 2016) - Dixon, Damon B.; Mackey-Bojack, Shannon M.; Sivanandam, Shanthi
Abstract: We report a case of Uhl's anomaly imaged at 19 weeks of gestation by fetal echocardiography with pathological confirmation by anatomical gross heart specimen and tissue histology. Uhl's anomaly of the right ventricle is a rare cardiac disorder with isolated right ventricular enlargement with almost complete absence of the right ventricular myocardium.